Transparent SiO2 aerogels prepared by ambient pressure drying with ternary azeotropes as components of pore fluid - Shlyakhtina, An.; Oh, Young-Jei (ELSEVIER SCIENCE BV, 2008)
Transparent SiO2 aerogels were prepared by two-step sol-gel processing followed by ambient pressure drying at temperatures from 70 to 250 degrees C. The wet gels were synthesized via acid-base catalysis using tetraethyl orthosilicate as a silica precursor and isopropanol as a solvent. Isopropanol was exchanged with n-butanol, and the gel surface was modified using a trimethylchlorosilane solution in n-butanol. Next, the solvent was exchanged in several steps with saturated hydrocarbon in order to obtain pore fluids containing azeotropic mixtures of water, n-butanol and a corresponding hydrocarbon (hexane, heptane, octane, nonane). Ambient pressure drying was performed in two steps, at the boiling points of the ternary azeotropes and hydrocarbons, respectively. In this way, transparent, crack-free aerogels of different shapes, with a specific surface area of 1000 m(2)/g, average pore diameter of similar to 40-55 angstrom and density in the range 0.4-0.57 g/cm(3) were obtained. (c) 2007 Published by Elsevier B.V.
Keywords: SILICA AEROGELS; OXIDE AEROGELS; GEL